2011
DOI: 10.1080/09593330.2011.587024
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasmid in diesel oil degradation by yeast species isolated from petroleum hydrocarbon-contaminated soil

Abstract: Five yeast species, namely Candida tropicalis, Cryptococcus laurentii, Trichosporon asahii, Rhodotorula mucilaginosa and Candida rugosa isolated from hydrocarbon-contaminated soil were found to be potent degraders of diesel oil. These microorganisms showed the presence of enzymes cytochrome P450, NADPH cytochrome c reductase, aminopyrine N demethylase, alcohol dehydrogenase, aldehyde dehydrogenase, naphthalene dioxygenase, catalase and glutathione S transferase when the cells were incubated for 48 h in Bushnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 30 publications
3
67
0
Order By: Relevance
“…Biosurfactants are widely used in hydrocarbon bioremediation field since they can enhance the growth on hydrophobic surface and can increase the nutrient uptake of hydrophobic substrates, thereby overcoming the poor availability of hydrocarbon contaminants to microorganisms [3]. Microorganisms having diverse synthetic capabilities, offer potential in expanding the range of surfactant with novel compounds, thereby providing new possible applications.…”
Section: Discussionmentioning
confidence: 99%
“…Biosurfactants are widely used in hydrocarbon bioremediation field since they can enhance the growth on hydrophobic surface and can increase the nutrient uptake of hydrophobic substrates, thereby overcoming the poor availability of hydrocarbon contaminants to microorganisms [3]. Microorganisms having diverse synthetic capabilities, offer potential in expanding the range of surfactant with novel compounds, thereby providing new possible applications.…”
Section: Discussionmentioning
confidence: 99%
“…Zones formed after incubation with free cells filtrate, suggest that these types of bacteria produce extracellular compounds that break oil and produce clearing zones. Chandran and Das (2010) concluded that culture supernatant of Trichosporon asahii (yeast) when inoculated with diesel oil, produced clear halo. Rodrigues et al (2006) correlated higher surface activity of biosurfactant solution with larger diameter produced by Lactococcus lactis.…”
Section: Discussionmentioning
confidence: 99%
“…This waste product is an interesting and inexpensive renewable carbon source for microbial fermentation to reducing bulk wastage of fruits. Among the microorganisms used in biosurfactant production, Pseudomonas species are the best known to grow in various substrates to produce rhamnolipids (Chandran and Das, 2010). This research work aimed to utilize cashew (A. occidentale) bagasse as substrates for P. aeruginosa to produce biosurfactants thereby converting low cost waste materials of environmental into products of superior value.…”
Section: Introductionmentioning
confidence: 99%
“…They are helpful in the uptake and utilization of hydrocarbons to facilitate the biodegradation of toxic hydrocarbons. Other advantages include eco-friendly nature, high foaming capacity, and efficiency at variable temperatures, pH and salt concentrations (Salihu et al, 2009;Chandran and Das, 2010).…”
Section: Introductionmentioning
confidence: 99%